Current Situation and Implications for Household Welfare - World Bank (World Bank, Washington, DC, 2020)
While Myanmar responded early and decisively to the COVID-19 pandemic thereby limiting adverse health impacts, evidence from the Myanmar COVID-19 Monitoring Platform shows that impacts on households’ welfare were significant. Border movement restrictions starting in February and a complete lockdown between March and April forced non-essential businesses to cease operations and prevented people from traveling to work. Meanwhile, about 100,000 economic migrants returned from Thailand alone. As a result, in May 2020, about 54 percent of households’ main workers reported not working and about 16 percent of firms had temporarily closed. The easing of restrictions between May and August contributed to a partial rebound of the economy, which is still suffering from the impact of reduced global demand, border trade disruptions, and potential changes in consumer behaviors.